Testing the Workload Measurement Analysis (WMA) Application at Aminah Islamic Hospital in Blitar Using the Technology Acceptance Model (TAM) Method - Raihan Akbar, Muhammad; Rahma Dahlia, Andina; Herina Putri, Antin; Allan Karunia Sakti, Dea; Athur Rosyida, Shofa (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2023)
The Workload Measurement Analysis (WMA) application is an Android-based information system that can be accessed online and applied in the healthcare sector. Two workload calculation methods are available: the Workload Indicator Staffing Need (WISN) method and the Health Workload Analysis (ABK Kes). The WMA application was tested using the Technology Acceptance Model (TAM) method, using systematic in-depth interviews. The Technology Acceptance Model (TAM) test had two main themes: usefulness analysis and ease of use analysis. The test included the login menu, homepage, learn page, data input, conclusion, and history. The Technology Acceptance Model (TAM) test yielded satisfactory results for both the ease of use and the usefulness analysis of the WMA application. It can be concluded that the WMA application is useful and easy to implement at Aminah Islamic Hospital in Blitar for calculating workload analysis, particularly for medical records.